Gene expression profiling on effect of aspirin on osteogenic differentiation of periodontal ligament stem cells - Fazliny Abd Rahman (Nature Publishing Group, 2021)
Abstract Periodontal ligament (PDL) contains a unique population of mesenchymal stem cells (MSCs), also known as PDL stem cells (PDLSCs). The regenerative properties of PDLSCs hold great potential for its use in stem cells based therapy, particularly for periodontal or bone regeneration. The present study investigated the global gene expression profile in PDLSCs during osteogenic differentiation. MSCs from PDL were isolated from normal permanent human teeth (n = 3). Microarray analysis was used to study the effects of ASA (200, 500, and 1000 μM) on the gene expression profiles in PDLSCs during osteogenic differentiation. Microarray study revealed that ASA was able to modulate PDLSCs gene expression profile. At 200 µM, 315 genes were dysregulated genes (DE), involving 151 upregulated and 164 downregulated genes. At 500 µM, 794 genes were DE, involving of 364 upregulated and 430 downregulated genes. At 1000 µM, the number of DE genes increased to 2035, of which 735 were upregulated and 1300 were downregulated. Bioinformatics analyses of the gene expression data revealed that the majority of DE genes (for 500 and 1000 µM ASA treatment) are involved in osteogenic differentiation. The gene network analysis was carried out using Ingenuity Pathway Analysis (IPA) software, and this revealed that the number of gene groups involved in cell adhesion and extracellular matrix components were increased. This study indicated that ASA could enhance PDLSCs functions and provide evidence for the potential use of ASA with PDLSCs for regenerative dentistry applications, particularly in the areas of periodontal health and regeneration. Periodontal ligament stem cells (PDLSCs) Aspirin (ASA) Microarray Osteogenic